2017
DOI: 10.1097/mca.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor clinical outcomes after successful chronic total occlusion intervention with drug-eluting stents

Abstract: Clinical parameters such as age, diabetes, and heart failure were independent predictors of the composite of cardiac death, myocardial infarction, and stent thrombosis, whereas angiographic or procedural parameters such as lesion length and number of implanted stents were predictors of target-vessel revascularization. Clinical outcomes after CTO intervention were worse in patients with multiple risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Besides, CKD was not routinely evaluated among CTO patients in previous studies. 26 , 33 , 36 In present study, only 51 (7%) patients were with CKD in successful CTO PCI group in our study, and the mean contrast volume was 227mL. Hydration, before and after the CTO procedure, was effective to reduce the occurrence of CIN.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Besides, CKD was not routinely evaluated among CTO patients in previous studies. 26 , 33 , 36 In present study, only 51 (7%) patients were with CKD in successful CTO PCI group in our study, and the mean contrast volume was 227mL. Hydration, before and after the CTO procedure, was effective to reduce the occurrence of CIN.…”
Section: Discussionmentioning
confidence: 50%
“… 24 Herein, diabetes mellitus was associated with MACE, consistent with previous reports. 25 , 26 Diabetic patients have more comorbidities, significant atherosclerotic burden, longer and more complex coronary lesions, and more adverse cardiovascular events, probably due to frequent hyperplasia, platelet hyperreactivity, increased fibrinogen levels, thromboxane, proinflammatory states, systemic endothelial dysfunction, and metabolic disorders. 27 , 28 Notably, collateral circulation development is less common in diabetic patients than in non-diabetic patients when coronary arteries become occluded.…”
Section: Discussionmentioning
confidence: 99%
“…IVUS-XPL (lesion length > 28 mm) and CTO-IVUS clinical trials have both shown significant reductions in MACE with IVUS. [31][32][33] In IVUS-XPL trial, major adverse cardiac events at 5 years occurred in 36 patients (5.6%) receiving IVUS guided PCI and in 70 patients (10.7%) receiving angiographic guidance (hazard ratio: 0.50; 95% confidence interval: 0.34 to 0.75; p = 0.001). 33 Further, in a randomized control clinical trial of 402 CTO procedures, MACE was significantly lower in IVUS guided PCI group compared with angiographic guided group (2.6% vs. 7.1%, p = 0.035; HR: 0.35, CI: 0.13-0.97).…”
Section: Discussionmentioning
confidence: 99%
“…Чем длиннее поражение, тем ниже частота успеха. Представленные данные согласуются с результатами других авторов и показывают, что длина ХОКА >30 мм служит предиктором безуспешного ЧКВ ХОКА [30,31]. В случае длинных ХОКА чаще приходится прибегать к ретроградной реканализации через систему коллатеральных ветвей.…”
Section: Discussionunclassified